CULTURE, MEMORY AND MEDIA : A STUDY OF CONTEMPORARY PAINTINGS FROM NAGALAND - Alinger, Lemtila; Imsong, Talisenla (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The paper examines the significance of visual art in the context of Nagaland, how during a time in the past, traditional visual and material art served to retain and externalise cultural memory, and now in the modern context, due to a phasing out of the older culture, other media have been necessitated to take its place. The study considers painting as a media that has come to perform a similar function providing continuity. The research is a qualitative study which examines the traditional material arts and culture of the Nagas as media of communication. For its theoretical basis, the study takes from Jan and Aleida Assmann’s (1991) concept of Cultural Memory and communicative memory, to study painting in the contemporary Naga context, as a media that offers a site for both these registers of memory to interact. Here established cultural ideas and metaphorsresurface and are re-presented in the light of contemporary conceptions and identities. The findings show that painting is a viable media for today for expressing and negotiating cultural memory and provides an alternative media,standing in for traditional artefacts or material signifiers, continuing to be a means for culture to remember and speak for itself.